ENERGY-INFORMATION APPROACH FOR FINDING DYNAMICAL PROCESS PATTERN - O. M. Gerget; V. A. Kochegurov (Бюллетень сибирской медицины)
The purpose of the research is developing of approaches and criterias that allow obtaining individual health value. Existing methods of diagnosing may be divided into two categories: statistic methods and functional dependency, based on metabolic energy-information process that takes place in organism.There is no doubt that wide spread statistic methods are beneficial and in most cases allow recognizing general trend of researched processes. But all statistic approaches share same drawback, they do not allow taking evincive conclusion while individual diagnosing and grading physician's impact in dynamics. Thus we face necessity for developing new ways of diagnosing, allowing individual health evaluating based on common trend. This task may be subdivided into: find common trend and recognize informative variables; identify anomalies and form homogeneous groups; apply methods to obtain average values, adequately revealing group functioning.The article, based on systematic approach, describes technology presenting the results of observations and child’s body is presented as complex dynamical system, that includes all required elements for the sustained functioning under external environment condition. Energy-informative approach is used for synthesizing generalized criteria for evaluating the functioning of dynamical biosystems.Given developed criteria and coefficients revealing the degree of tension in the body under normal functioning conditions. The average groups coefficient values are taken into consideration. Described energy-information approach enables determine state of normal or pathology functioning that may be crucial for children.Application of energy-information approach to evaluate the functioning of dynamic systems, allows recognizing common trend of researched objects and obtain individual health values. Such tasks are faced by practical and evidence-based medicine – finding individual health values, based on analysis of common trend of functioning.